Dysregulation of BCL-2 family proteins in blood neoplasm: therapeutic relevance of antineoplastic agent venetoclax - Faris Tayeb (Open Exploration Publishing Inc., 2024)
During cellular stress, the master regulators of intrinsic self-death (apoptosis) are BCL-2 family proteins. The BCL-2 family proteins play a key role in apoptosis and are tightly regulated via other BCL-2 family proteins, non-BCL-2 protein suppressors, and epigenetic modifications. As the name implies, these proteins possess one or two of the four BCL-2 homology domains (BH1-BH4). According to their roles, they are classified as pro-apoptotic or pro-survival proteins. BH-3-only proteins possess a single BH3 domain and are specific/key effector proteins for intracellular death commitment, particularly in the context of cell survival and programmed cell death. This delicate interplay among the BCL-2 family members is essential for maintaining the primary hemostasis, or balance, of cell fate. The anti-apoptotic proteins, such as BCL-2 and BCL-XL, promote cell survival by inhibiting apoptosis. On the other hand, the pro-apoptotic proteins, such as BAX and BAK, drive apoptosis. It ensures that cells are able to respond appropriately to various internal and external signals, ultimately determining whether a cell survives or undergoes programmed cell death. Understanding and targeting this delicate balance is a promising avenue for developing therapeutic strategies to modulate cell fate and treat various diseases. The molecular pathogenesis of BCL-2 family proteins in blood disorders involves differential expression of these components resulting in the dysregulation of the pathway contributing to cell survival and resistance to apoptosis as observed in follicular lymphoma, diffuse large B-cell lymphoma, acute lymphoblastic leukemia, and acute myeloid leukemia. Such dysregulation is a major impediment to standard therapies and aids in chemo resistance. Studies show some promising clinical outcomes with antineoplastic agent venetoclax either as a monotherapy or in combination with other agents. This review discusses recent studies on the regulation of BCL-2 family proteins which might provide a molecular landscape for their clinical implications in blood disorders.